Critical cracking thickness of calcium phosphates biomimetic coating: Verification via a Singh-Tirumkudulu model. Issue 17 (1st December 2017) - Xia, Wei; Fu, Le; Engqvist, Håkan
Abstract: Despite the many advantages of biomimetic calcium phosphates (CaPs) coatings, there is a troublesome problem of low cohesion in the coatings. The low cohesion originates from the absence of bonding between CaP crystals, leading to cracks during drying of the coatings. In this study, based on a simplified Singh-Tirumkudulu model, the critical cracking thickness (CCT) of biomimetic CaPs coatings has been calculated. CaPs crystal size is the key factor influencing the CCT, except for the particle's shear modulus. Biomimetic CaPs coatings with different thickness have been prepared by soaking Ti substrates with a transition layer of TiO2 (rutile) in Dulbecco's phosphate buffer saline solution (DPBS) for 1, 2, 4 and 6 weeks. The morphology, thickness, and whether cracks formed or not were evaluated by SEM. The simplified Singh and Tirumkudulu model has been verified in terms of our experimental results and data obtained from previous literatures. Via dedicated experiments and calculations it is concluded that a thickness of about approximately 2 µm is the critical value for a crack-free CaPs coating given that the CaPs crystal size is smaller than 100 nm. The model could be used in the future design of crack-free biomimetic coatings.